Exigência em metionina para juvenis de jundiá - Rotili, Daniel Antonio (2014)
This work aimed to evaluate the digestibility of ingredients and estimate the nutritional requirement of methionine for juvenile catfish (Rhamdia quelen). For this a digestibility trial was carried out by determining the apparent digestibility coefficients (ADC) of dry matter (DM), crude protein (CP) and gross energy (GE) of ingredients: catfishes flour (FJ), commercial fishmeal (FPC) of meat and bone meal (MBM), soybean protein concentrate (SPC), maltodextrin (M), corn starch (AM), gelatin (G) and casein (C) for juvenile catfish (weight 35.45 ± 12.1 g), through a reference diet (RD) and test diets (diet with 70% of DR over 30% of the tested ingredient) containing 0.3% chromic oxide as an inert marker. The digestibility coefficients were adjusted to compensate for the partial loss of nutrients through leaching by water. Ingredients test FPC, FJ, M, C and G showed higher DM, 77.03 to 95.66%, for PB the CPS showed lower digestibility (59.70%) compared to the other ingredients FPC, FCO, FJ, G and C were 87.19 to 99.59%, as well as for EB the CPS showed lower digestibility 71.59% did not differ AM with 73,59%, being the ingredients FCO, FJ, FPC, G and C with higher digestibility, with 82.70 to 85.79%. Subsequently a dose response test was conducted to estimate the methionine requirement of juvenile catfish (initial weight of 3.26 ± 0.3 g and medium length 7.17 ± 0.27 cm), using 35 animals per experimental unit, and four replications. Six isoproteic and isocaloric diets were formulated with six increasing levels of methionine (0.9, 1.6, 2.3, 3.0, 3.7 and 4.4% crude protein) holding constant the level of cystine (0 , 19% in crude protein). Each diet for fish were distributed randomly, provided twice daily (9:30 and 17:00) until apparent satiation, during 15 weeks. The values of relative weight gain (RWG) and specific growth rate (SGR) increased up to 3.0% of methionine (P <0.05) and being kept virtually the same later. The rate of protein retention increased up to 2.3% methionine level, but decreasing in the 4.4% level (P <0.05). The quadratic regression analysis on the RWG and SGR indicated that optimal levels of methionine in the diet recommended for the growth of juvenile catfish, are estimated at 3.59% and 3.46% in crude protein, respectively, and maintaining a constant level of cystine (0.19% in crude protein), thus corresponding to 1.33 and 1.28% in the diet, or total sulfur amino acid to 3.65 and 3.78% in the crude protein, respectively.